Adult Learners Needs, Problems, Disabilities, Development and Solutions. Bibliographical Review 1978-1987 - Johnson, Calvin; Arkansas Univ., Little Rock. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
This report provides an abstracted review of 75 available sources on the subject of adult learning problems, disabilities, development, and solutions in adult education. Documents from many levels of education are included; most of the works cited are unpublished reports, papers, and dissertations. Entries are arranged in chronological order beginning with the most recent work and extending back to 1978. (The exception to this order is the separate listing of unsigned works that is the final section of this review.) Each entry includes an ERIC (Educational Resources Information Center) Document Reproduction Service number. (KC)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Basic Education; Adult Development; Adult Education; Adult Learning; Adult Literacy; Adult Programs; Adult Students; Annotated Bibliographies; Educational Policy; Educational Research; High School Equivalency Programs; Learning Disabilities; Postsecondary Education; Research Utilization; Reference Materials, Bibliographies